Relationship Between Knowledge Level And Selection Of Long-Term Contraception Methods In Wus At Pmb Rubiyati - Lailatul Hidayah; Melyana Nurul Widyawati; Sri Rahayu (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
ABSTRAKBackground : Family Planning is also one of the most effective ways to increase family resilience, health and safety of mothers, children, and women. Family planning acceptors in Temanggung Regency prefer to use non-MKJP family planning. This study aims to determine the relationship between the level of knowledge and the selection of long-term contraceptive methods in WUS at PMB Rubiyati.Research Methods: This research is a correlation analytic study with a cross sectional approach. This research was conducted at PMB Rubiyati. The population in this study were 43 active family planning acceptors in March 2021 at PMB Rubiyati. How to collect data by means of questionnaires or questionnaires using googleform. Data analysis used univariate and bivariate analysis using Chi Square.Research Results: Based on the results of statistical tests using chi square with p value = 0.003. So H0 is rejected, which means that there is a knowledge relationship in the selection of long-term contraceptive methods in women of childbearing age at PMB Rubiyati.Conclusion : There is a relationship between knowledge and the choice of long-term contraceptive methods.